2008
DOI: 10.1177/154193120805200305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Task Performance and Task Complexity on the Validity of Computational Models of Attention

Abstract: Computational models of attention can be used as a component of decision support systems. For accurate support, a computational model of attention has to be valid and robust. The effects of task performance and task complexity on the validity of three different computational models of attention were investigated in an experiment. The gaze-based model uses gaze behavior to determine where the subject's attention is, the task-based model uses information about the task and the combined model uses both gaze behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The chosen approach was to offer a human certain demanding tasks, measure its performance and several physiological data, feed these data into the model, and compare the output of the model with self-reports of the participants (similar to Ref. 25). This provides external validation of the model, by providing realistic parameter settings for different types of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The chosen approach was to offer a human certain demanding tasks, measure its performance and several physiological data, feed these data into the model, and compare the output of the model with self-reports of the participants (similar to Ref. 25). This provides external validation of the model, by providing realistic parameter settings for different types of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The final results indicated that the complexity of the task led to significant differences in the employee's operational performance. De Koning et al (2008) researched the influence of task complexity and task performance on the validity of computational models of attention. The experiment included 22 male students and 20 female students.…”
Section: Introductionmentioning
confidence: 99%